Thoughts on the Dacians of the Romanian Historical Imaginary - FLOREA, Gelu A. (Studia Universitatis Babeș-Bolyai Historia, 2019)
The paper is presenting some of the main issues concerning the “public image” of the Dacians in Romanian common thought and knowledge and is aiming to identify the sources of this vulgate set of representations of ancestors. The collective imaginary of the general public concerning the Dacians is partially fuelled by the scholarly literature and thus reflects some aspects of the archaeological discourse. However, archaeological research today is defined by a methodological approach which has an opposite direction, whereby the reconstruction of the past starts at the level of the micro-communities, of particular facts and regional features instead of levelling generalization. This seems to represent the essence of the divergence between the scientific approach characterized by a critical disposition and moderate scepticism on the one hand, and profoundly subjective traditionalist representations of the collective imaginary on the other. Rezumat: Reflecţii cu privire la dacii imaginarului istoric românesc. Acest articol prezintă câteva dintre problemele principale referitoare la imaginea publică a dacilor în cultura de masă şi în discursul ştiinţific din România, încercând să identifice sursele acestei imagini vulgarizate a strămoşilor. Imaginarul colectiv este alimentat parţial de literatura academică şi, ca urmare, el reflectă anumite aspecte ale discursului arheologic. Cu toate acestea, cercetarea arheologică de astăzi este caracterizată de o abordare metodologică de sens contrar, în care reconstruirea trecutului pleacă de la nivelul micro-comunităţilor, al faptelor particulare şi al trăsăturilor regionale, respingând generalizările şi interpretările lipsite de nuanţe. Aceasta pare să reprezinte esenţa clivajului dintre abordarea ştiinţifică, definită de spirit critic şi de un scepticism moderat, pe de o parte, şi reprezentările tradiţionaliste, profund subiective, ale imaginarului colectiv, de cealaltă parte. Cuvinte-cheie: daci, dacism, protocronism, imaginar istoric, stereotipuri.